Sex Steroids Modulate Uterine-Placental Vasculature: Implications for Obstetrics and Neonatal Outcomes - Maliqueo, Manuel; Echiburú, Bárbara; Crisosto, Nicolás (Frontiers in Physiology, 2016)
Adequate blood supply to the uterine-placental region is crucial to ensure the transport of oxygen and nutrients to the growing fetus. Multiple factors intervene to achieve appropriate uterine blood flow and the structuring of the placental vasculature during the early stages of pregnancy. Among these factors, oxygen concentrations, growth factors, cytokines and steroid hormones are the most important. Sex steroids are present in extremely high concentrations in the maternal circulation and are important paracrine and autocrine regulators of a wide range of maternal and placental functions. In this regard, progesterone and estrogens act as modulators of uterine vessels and decrease the resistance of the spiral uterine arteries. On the other hand, androgens have the opposite effect, increasing the vascular resistance of the uterus. Moreover, progesterone and estrogens modulate the synthesis and release of angiogenic factors by placental cells, which regulates trophoblastic invasion and uterine artery remodeling. In this scenario, it is not surprising that women with pregnancy-related pathologies, such as early miscarriages, preterm delivery, preeclampsia and fetal growth restriction, exhibit altered sex steroid concentrations.